OPTIMALISASI PENGETAHUAN PEKERJA MELALUI EDUKASI POSISI ERGONOMI DI SATUAN PELAYANAN PEMENUHAN GIZI - Eliyana Eliyana; Nafilah Nafilah; Andini Dian; Lovyta Wulandari; Rizathul Rizqi (Institut Kesehatan Yarsi Mataram, 2026)
The main problem identified was that many workers still performed work activities using non-ergonomic postures, such as bending for prolonged periods, sitting in low positions, and rarely performing stretching exercises, which increased the risk of back pain and muscle fatigue. This community service activity aimed to improve workers’ knowledge regarding ergonomic working positions as an effort to prevent musculoskeletal disorders among 14 workers at the Satuan Pelayanan Pemenuhan Gizi (SPPG) Purin. The activity included observation, pre-test, ergonomic education using poster media, demonstrations of proper posture and stretching exercises, followed by post-test and evaluation.The results showed improved workers’ knowledge after the intervention. Before the intervention, most workers had a moderate level of knowledge (85.72%), while after the program, 64.29% of workers achieved a high level of knowledge and none remained in low category. Workers also reported a better understanding of proper working methods and the importance of maintaining correct body posture while working. Ergonomic education through poster media and demonstrations effectively increased worker’s knowledge and may help prevent musculoskeletal disorders while promoting occupational safety and productivity.